A comprehensive analysis on cigarettes smoking and its determinants in Bangladesh using logistic regression model - Rumana, Afrin Sadia; Khatun, Asia; Das, Sukanta (International Journal of Research in Medical Sciences, 2020)
Background: In Bangladesh, smoking is one of the leading preventable causes of death. Despite possessing knowledge about the consequences of smoking and the resultant non-communicable diseases, individuals have become considerably habituated to it. The study aims to identify the factors associated with smoking cigarettes and as well as to examine the existing situation of this issue among adult males in Bangladesh. Methods: Total 480 adult males were surveyed from Bangladesh through personal interview and online questionnaire, (from June 2018 to June 2019). To measure the effect of the explanatory variables on cigarettes smoking, authors perform χ2 test of independence as bivariate analysis. After performing bivariate analysis, a logistic regression analysis has been performed to assess the effect of the explanatory variables. Results: Findings of the study revealed that educational level, household economic status, media exposure, division have significant contribution for smoking cigarettes among the adult male in Bangladesh. A comparison of religious affiliation showed smoking cigarettes to be higher among non-muslim counterparts. Respondents living in rural area are found to have smoking cigarettes comparing with urban area. Conclusions: From the study it can be concluded that education and socio-economic status of male make a significant contribution in cigarettes smoking.